Ukraine in Transformation From Soviet Republic to European Society - Veira-Ramos, Alberto; Liubyva, Tetiana; Golovakha, Evgenii (Springer International Publishing : Imprint: Palgrave Macmillan, 2020)
XX, 282 p. 26 illus., 12 illus. in color.